2012
DOI: 10.1038/labinvest.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

Impaired post-infarction cardiac remodeling in chronic kidney disease is due to excessive renin release

Abstract: The complex pathophysiological interactions between heart and kidney diseases are collectively known as cardiorenal syndrome. The renin-angiotensin system (RAS) may have a pivotal role in the development of cardiorenal syndrome. The aim of this study was to elucidate the RAS activity responsible for adverse post-infarction remodeling and prognosis in mice with renal failure. To establish the type IV cardiorenal syndrome model, 5/6 nephrectomy (NTX) was performed in a surgical procedure, followed by the inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The STNx was accomplished by a two-step surgical procedure, with an interval of one week between the steps; for each step the mice were anesthetized by intraperitoneal injection of pentobarbital (50mg/kg), [17]. In the first step, two to three arterial branches of the left kidney were ligated, leaving an intact kidney segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The STNx was accomplished by a two-step surgical procedure, with an interval of one week between the steps; for each step the mice were anesthetized by intraperitoneal injection of pentobarbital (50mg/kg), [17]. In the first step, two to three arterial branches of the left kidney were ligated, leaving an intact kidney segment.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, LV ejection fraction (EF) value, fractional shortening (FS), and LV mass were calculated, as previously described [19]. All measurements were repeated thrice from at least 10 consecutive cardiac cycles, and were analyzed by a single observer blinded to the treatment protocol, according to the recommendations of the American Society of Echocardiography [17, 20]. The mean values were used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“… 90 The renin-angiotensin system (RAS), a signaling cascade responsible for regulating blood pressure, has a well-established critical role in cardio-renal syndrome. 91 Ogawa et al 92 reported that nephrectomy in mice with an MI influenced cardiac remodeling after the MI. The combination of nephrectomy and MI resulted in deteriorated left ventricular remodeling and RAS activation, oxidative stress and MCP-1.…”
Section: Crosstalk Between the Heart And Kidney: Cardio-renal Axismentioning
confidence: 99%
“…Real-time PCR in a Step One real-time PCR system (Applied Biosystems) was used to determine the mRNA expression of IFN-␥ (Assay ID: Rn99999014_m1), IL-2 (Assay ID: Rn00587673_m1), and MCP-1 (Assay ID: Rn00580555_m1) and 18s rRNA (Assay ID: Hs99999901_s1) as a control. cDNA was run in duplicates, quantitative data were calculated using the comparative CT (⌬⌬CT) method, and the mRNA expression was normalized by normal rat hearts (28,32).…”
Section: Induction Of Eammentioning
confidence: 99%